Sulfide removal from petroleum refinery wastewater using pseudomonas putida (ATCC 49128) and bacillus cereus (ATCC 14579) - Ahmad, Mani Malam (2018)
Hydrogen sulfide (H2S) has been recognized as one of the hazardous pollutants from petroleum refinery based wastewater (PRW), with reported cases of environmental and economic challenges, besides other human health complications. The heterogeneous nature of PRW couple with the documented shortfalls of the classical physicochemical mitigation approaches was behind the quest for a cost-effective and eco-friendly alternative with minimum adverse effects. A novel integrated bacterial mixed culture (BMC), Pseudomonas putida (ATCC 49128) and Bacillus cereus (ATCC 14579) with traceable imprints in biodegradation of high-strength PRW proposed as a suitable alternative sulfide oxidation approach with a potential solution to the shortfalls. Their complementary helper effects could be the reason behind their tolerance to the H2S inhibitory effect. Initially, the impact of nutrient concentration and other physical operating conditions of temperature, agitation and acclimatization time to the isolates growth were screened and subsequently optimized in shake flasks with the aid of Design-Expert software. Based on these optimized growth conditions, relative removal efficiency RE of BMC along with the corresponding pure cultures were carried out using simulated wastewater at different concentrations (200, 300 and 500 ppm). The RE of the pure and mixed-culture models was found to be 95%–100% with simulated wastewater in shake flasks. However, a sustained RE was displayed by the selected model (BMC), with the highest RE of 99% in 500 ppm of S−2 within the HRT of 24 hours. Furthermore, the synergistic contribution effects of the batch culture process parameters on the BMC sulfide oxidation were optimized at three coded levels using face-centered central composite design (FCCCD) and response surface methodology (RSM) statistical tools. The highest RE of 91% was obtained with the BMC model at optimum process parameters of influent sulfide concentration, aeration, temperature, and agitation of 500 ppm, 0.5 vvm, 30 °C, and 140 rpm, respectively, within 8 hours of HRT. Moreover, the sulfide biodegradation capability of BMC was validated using the actual PRW based on the optimum parameters which resulted in overwhelming RE values of 98.76%–99.75%. Conclusively, the findings fill in some gaps concerning the biological sulfide oxidation from recalcitrant PRW by a novel BMC model in a lab-scale batch culture aerobic bioreactor. It suggested that the reliability and prediction ability of this eco-friendly model is therefore suitable for treating high-strength sulfide-laden wastewater with potential capabilities of maximum RE.